The work and thinking of Stavros Zoumboulakis - Δημητρακάκης Γιάννης (Ariadne, 2021)
THIS essay is based on the speech made at the award ceremony honoring Stavros Zoumboulakis with the title of Doctor Honoris Causa of the Department of Philology at the University of Crete (Rethymnon, 3 December 2019). The purpose of the essay is to discuss Zoumboulakis’ contribution to literary studies, as well as to focus on important aspects of his engagement as a public intellectual. Zoumboulakis was the chief editor of Nea Hestia, the longest-running Greek literary review, from 1998 until 2012. During his editorship, Nea Hestia exerted considerable influence on intellectual life in Greece. In many of his essays Zoumboulakis explores the connection between literature and ethics. He has shown a strong interest in European and American novels written by Jewish and Christian authors and he deals with topics such as the history of Judaism, antisemitism and the Holocaust. He has examined the pivotal role of Christianity in the historical development of hatred against Jews and he has contributed to the ongoing debate on questions regarding the philosophical and theological implications of the Holocaust. Another of his permanent concerns is the complex relationship between religion and modernity; he mainly discusses the long and difficult process of reconciliation between Christian faith and the principles of modern democracy. He also argues that it is only the secular state (l’état laïque) that can guarantee the peaceful coexistence of believers of the three monotheistic religions.